PENERAPAN STRATEGI PEMBELAJARAN AKTIF UNTUK MENINGKATKAN NILAI AGAMA ISLAM PADA ANAK USIA DINI USIA 4-5 TAHUN - Suranto, Muh.; Anggriani, Putri Fathonah (Jurnal Ilmiah Pendidikan dan Keislaman, 2022)
The age of 0-6 years children is known as the golden period where at this time the child's development is quite rapid so that at this time the environment must provide good stimulation. TKIT Insan Harapan is a PAUD institution that applies active learning strategies to increase the value of Islam in its students. Ages 4-5 in living religious values are still influenced by fantasy and emotions. Children almost all of their activities are playing exploring objects around which are certainly fun so teachers need active learning strategies to increase the value of the Islamic religion. Aspects of the development of Islamic religious values develop well, of course, with the role of teachers who provide balance through activities by carrying out learning strategies in order to achieve goals. In this study, it uses qualitative research methods, namely in collecting researcher data using observation techniques, interviews and documentation. The results showed that active learning strategies to increase the value of Islam in TKIT Insan Hrapan used picture and picture strategies, singing, true or false, storytelling and card sort and there were several supporting and inhibiting factors for learning strategies